1993
DOI: 10.1136/pgmj.69.814.653
|View full text |Cite
|
Sign up to set email alerts
|

Haemolytic-uraemic syndrome with thrombotic microangiopathy of the retina following cytomegalovirus infection: postmortem findings

Abstract: Summary:Haemolytic-uraemic syndrome is characterized by thrombotic microangiopathy of the glomeruli and smaller arterial vessels of the kidney. Extrarenal thrombotic microangiopathy occurs, but ocular involvement is rarely demonstrated microscopically. We describe a 33 year old woman with a 3 week febrile episode and seropositivity for cytomegalovirus infection who developed acute renal failure, blindness and severe encephalopathy which was the cause ofdeath. Thrombotic microangiopathy ofretinal vessels may be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1996
1996
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Neau et al (13) reported a 30‐year‐old female with primary CMV infection complicated by microangiopathic hemolytic anemia and neurologic symptoms, but without renal failure, who responded to high‐dose corticosteroids, blood plasma transfusions, and foscarnet. Caton et al (14) described a 37‐year‐old female with acute CMV infection, microangiopathic hemolytic anemia, acute renal failure, and severe encephalopathy. The patient was treated with corticosteroids, but ultimately died of consequences of hypoxic‐ischemic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Neau et al (13) reported a 30‐year‐old female with primary CMV infection complicated by microangiopathic hemolytic anemia and neurologic symptoms, but without renal failure, who responded to high‐dose corticosteroids, blood plasma transfusions, and foscarnet. Caton et al (14) described a 37‐year‐old female with acute CMV infection, microangiopathic hemolytic anemia, acute renal failure, and severe encephalopathy. The patient was treated with corticosteroids, but ultimately died of consequences of hypoxic‐ischemic encephalopathy.…”
Section: Discussionmentioning
confidence: 99%
“…It is unlikely that changes in anti-retroviral therapy triggered the onset of HUS.16 Severe hypertension was an early prominent sign in four cases, although the retinal features observed in two individuals were probably secondary to retinal vascular microangiopathy as they failed to resolve despite adequate antihypertensive therapy. 17 All patients received standard treatment for anaemia (blood transfusions) and required haemodialysis for renal support. Measures to limit vascular injury such as fresh frozen plasma and prostacyclin failed to arrest disease progression although the efficacy of these treatments remains to be determined.6 Unlike D+ HUS where glomerular thrombosis is the main pathology, intravascular thromboses involving arterioles and small arteries were noted and acute tubular necrosis reflecting extensive vascular occlusion was seen in three of the four cases examined.…”
Section: Discussionmentioning
confidence: 99%
“…For some infections, the pathogenesis of microangiopathic hemolytic anemia has been described. Examples are bacterial endocarditis, [62] bacterial infections associated with microvascular injury such as brucellosis [32,33] streptococcal infections resulting in acute glomerulonephritis, [66] angioinvasive fungi such as aspergillosis, [83], and viruses and rickettsiae that cause endothelial injury such as CMV, [71][72][73] HIV, [16] erlichiosis, [44] and Rocky Mountain spotted fever [56]. However for other infections the mechanisms of microangiopathic hemolytic anemia are unclear.…”
Section: Discussionmentioning
confidence: 99%